(3SbhW GdHGSJjds - (3OjeGS, CdcSfOQs; (3aQjO, Tajb CSYOs ((3GdbGgQIs (3CbdGe YQHjI ddfTQ hGdJhRjYs, 2023)
(3QhGjI JMcj HGdJaUjd hGbYI SbhW GdHGSJjd hGdeLRQI Jdc GdJi GQJcHJ ajgG hENQGL GMO Gge GdTNUjGJ GdeTLYI Ydi GdKhQI ef Pdc GdSLf hGdPj hVYJg ajg EeQCI JMbO Ydjg dCSHGH TNUjI aMSH dhLhO YdGbI HGdeGVj HjfgeG hGSJZdJ bQHgG ef GdedcI GdfeSGhjI eGQj GfJhGfjJ dGUOGQ GeQ EdbGFg HGdSLf hJhVM GdQhGjI eOi SPGLI Gdedc dhjS GdSGOS YTQ hSQYI GdhUhd Gdi Ybdg hGdJCKjQ Ydjgs
Keywords: (3GdCOH GdaQfSjs